Quercetin reduces illness but not immune perturbations after intensive exercise - Nieman, D. C.; Henson, D. A.; Gross, S. J.; Jenkins, D. P.; Davis, J. M.; Murphy, E. A.; Carmichael, M. D.; Dumke, C. L.; Utter, A. C.; McAnulty, S. R.; McAnulty, L. S.; Mayer, E. P. (Medicine & Science in Sports & Exercise, 2007)
Purpose: To investigate the effects of quercetin supplementation on incidence of upper respiratory tract infections (URTI) and exercise-induced changes in immune function.